(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Some post-experiment procedure was planned and implemented to research on the presence of vermicompost and NPK in the dry and fresh substance yield of wheat plants. Presence of 150gm of vermicompost and 5gm of NPK per Kg soil and their interaction with one another established the best fresh and dry matter gain in 45 days old wheat plants. This experiment was very significant as the value was almost 0.01 (P = 0.01) which was higher than all other values tested earlier.